Pentavalent Antimonials Combined with Other Therapeutic Alternatives for the Treatment of Cutaneous and Mucocutaneous Leishmaniasis: A Systematic Review - Taisa Rocha Navasconi Berbert; Tatiane França Perles de Mello; Priscila Wolf Nassif; Camila Alves Mota; Aline Verzignassi Silveira; Giovana Chiqueto Duarte; Izabel Galhardo Demarchi; Sandra Mara Alessi Aristides; Maria Valdrinez Campana Lonardoni; Jorge Juarez Vieira Teixeira; Thaís Gomes Verziganassi Silveira (Hindawi Limited, 2018)
The first choice drugs for the treatment of cutaneous and mucocutaneous leishmaniasis are pentavalent antimonials, sodium stibogluconate, or meglumine antimoniate. However, the treatment with these drugs is expensive, can cause serious adverse effects, and is not always effective. The combination of two drugs by different routes or the combination of an alternative therapy with systemic therapy can increase the efficacy and decrease the collateral effects caused by the reference drugs. In this systematic review we investigated publications that described a combination of nonconventional treatment for cutaneous and mucocutaneous with pentavalent antimonials. A literature review was performed in the databases Web of Knowledge and PubMed in the period from 01st of December 2004 to 01st of June 2017, according to Prisma statement. Only clinical trials involving the treatment for cutaneous or mucocutaneous leishmaniasis, in English, and with available abstract were added. Other types of publications, such as reviews, case reports, comments to the editor, letters, interviews, guidelines, and errata, were excluded. Sixteen articles were selected and the pentavalent antimonials were administered in combination with pentoxifylline, granulocyte macrophage colony-stimulating factor, imiquimod, intralesional sodium stibogluconate, ketoconazole, silver-containing polyester dressing, lyophilized LEISH-F1 protein, cryotherapy, topical honey, and omeprazole. In general, the combined therapy resulted in high rates of clinical cure and when relapse or recurrence was reported, it was higher in the groups treated with pentavalent antimonials alone. The majority of the articles included in this review showed that cure rate ranged from 70 to 100% in patients treated with the combinations. Serious adverse effects were not observed in patients treated with drugs combination. The combination of other drugs or treatment modalities with pentavalent antimonials has proved to be effective for cutaneous and mucocutaneous leishmaniasis and for most seemed to be safe. However, new randomized, controlled, and multicentric clinical trials with more robust samples should be performed, especially the combination with immunomodulators.